American Jezebel: The Uncommon Life of Anne Hutchinson, the Woman Who Defied the Puritans (HarperCollins, Pen & Sword Aviation, 2009)
In 1637, Anne Hutchinson, a forty-six-year-old midwife who was pregnant with her sixteenth child, stood before forty male judges of the Massachusetts General Court, charged with heresy and sedition. In a time when women could not vote, hold public office, or teach outside the home, the charismatic Hutchinson wielded remarkable political power. Her unconventional ideas had attracted a following of prominent citizens eager for social reform. Hutchinson defended herself brilliantly, but the judges, faced with a perceived threat to public order, banished her for behaving in a manner "not comely for [her] sex." Written by one of Hutchinson's direct descendants, American Jezebel brings both balance and perspective to Hutchinson's story. It captures this American heroine's life in all its complexity, presenting her not as a religious fanatic, a cardboard feminist, or a raging crank—as some have portrayed her—but as a flesh-and-blood wife, mother, theologian, and political leader. The book narrates her dramatic expulsion from Massachusetts, after which her judges, still threatened by her challenges, promptly built Harvard College to enforce religious and social orthodoxies—making her the mid-wife to the nation's first college. In exile, she settled Rhode Island, becoming the only woman ever to co-found an American colony. The seeds of the American struggle for women's and human rights can be found in the story of this one woman's courageous life. American Jezebel illuminates the origins of our modern concepts of religious freedom, equal rights, and free speech, and showcases an extraordinary woman whose achievements are astonishing by the standards of any era.

Hey America!: The Epic Story of Black Music and the White House (Pen & Sword Aviation, Birlinn, 2024)
This is the untold story of black music – its triumph over racism, segregation, undercapitalised record labels, media discrimination and political anxiety – told through the perspective of the most powerful office in the world: from Louis Armstrong's spat with President Eisenhower and Eartha Kitt's stormy encounter with Lady Bird Johnson to James Brown's flirtation with Nixon, Reaganomics and the 'Cop Killer' scandal. Moving, insightful and wide-ranging, Hey America! charts the evolution of sixties soul from the margins of American society to the mainstream, culminating in the rise of urban hip-hop and the dramatic stand-off between Donald Trump and the Black Lives Matter movement.

Parkland: Birth of a Movement (HarperCollins, Pen & Sword Aviation, 2019)
A New York Times Bestseller "A moving petition to America that it not look away from the catastrophes at Columbine, Newtown, Sandy Hook, Virginia Tech, and, yes, Parkland. It succeeds as an in-depth report about the "generational campaign" in the aftermath of the Parkland tragedy, a bi-partisan movement advocating serious gun reform." - Atlanta Journal-Constitution The acclaimed New York Times bestselling author of Columbine offers an intimate, deeply moving account of the extraordinary teenage survivors who became activists and pushed back against the NRA and feckless Congressional leaders-inspiring millions of Americans to join their grassroots #neveragain movement. Nineteen years ago, Dave Cullen was among the first to arrive at Columbine High, even before most of the SWAT teams went in. While writing his acclaimed account of the tragedy, he suffered two bouts of secondary PTSD. He covered all the later tragedies from a distance, working with a cadre of experts cultivated from academia and the FBI, but swore he would never return to the scene of a ghastly crime. But in March 2018, Cullen went to Marjory Stoneman Douglas High School because something radically different was happening. In nearly twenty years witnessing the mass shootings epidemic escalate, he was stunned and awed by the courage, anger, and conviction of the high school's students. Refusing to allow adults and the media to shape their story, these remarkable adolescents took control, using their grief as a catalyst for change, transforming tragedy into a movement of astonishing hope that has galvanized a nation. Cullen unfolds the story of Parkland through the voices of key participants whose diverse personalities and outlooks comprise every facet of the movement. Instead of taking us into the mind of the killer, he takes us into the hearts of the Douglas students as they cope with the common concerns of high school students everywhere-awaiting college acceptance letters, studying for mid-term exams, competing against their athletic rivals, putting together the yearbook, staging the musical Spring Awakening, enjoying prom and graduation-while moving forward from a horrific event that has altered them forever. Deeply researched and beautifully told, Parkland is an in-depth examination of this pivotal moment in American culture-and an up-close portrait that reveals what these extraordinary young people are like. As it celebrates the passion of these astonishing students who are making history, this spellbinding book is an inspiring call to action for lasting change.